2008
DOI: 10.1007/s11255-008-9475-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of female sexual function and quality of life in predialysis, peritoneal dialysis, hemodialysis, and renal transplant patients

Abstract: Introduction Chronic renal failure (CRF) and renal replacement treatments have a negative effect on sexual function and quality of life (QoL). The literature on female sexual dysfunction (FSD) in patients with CRF is limited. The aim of this study is to compare the sexual function and QoL in predialysis (PreD), dialysis, and transplant patients. Materials and methods A total of 106 women including 21 PreD, 45 dialysis, 20 renal transplantation (Tx), and 20 control patients were enrolled in the study. The Femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
78
5
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 23 publications
14
78
5
3
Order By: Relevance
“…This finding is consistent with the results of other studies showing that SD is more frequent in patients with chronic renal disease (3,4,35,36,37,38). In a study conducted with patients undergoing dialysis treatment, 65% of participants expressed dissatisfaction with their sexual life, 40% expressed that sexual intercourse does not arouse any more interest, and 25% expressed symptoms of probable SD (39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with the results of other studies showing that SD is more frequent in patients with chronic renal disease (3,4,35,36,37,38). In a study conducted with patients undergoing dialysis treatment, 65% of participants expressed dissatisfaction with their sexual life, 40% expressed that sexual intercourse does not arouse any more interest, and 25% expressed symptoms of probable SD (39).…”
Section: Discussionsupporting
confidence: 93%
“…It is frequently reported in studies that the quality of life is lower in patients with chronic renal disease, particularly in physical and psychological areas (3,7,8,9,41). Accordingly, the results of our study also support the literature data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[5] Basok et al using FSFI scores reported that the rates of FSD were 81, 66.7, and 50% in the PD and HD patients and control subjects, respectively. [17] We found that SD was 95.7% in female with ESRD patients (94.1% in PD; all of HD patients) and 45.8% in the control.…”
Section: Discussionmentioning
confidence: 55%
“…11 Successful transplantation is clearly the most effective means to restore normal sexual desire in women with chronic kidney failure. 12 …”
Section: Sexual Dysfunction In Womenmentioning
confidence: 99%